2018
DOI: 10.1177/0897190018795343
|View full text |Cite
|
Sign up to set email alerts
|

A Case Report of Cangrelor Bridge Therapy for a Diagnostic Bronchoscopy With Biopsy

Abstract: Although premature discontinuation of dual antiplatelet therapy (DAPT) is associated with an increased risk of ischemic complications, patients may present with an urgent need for surgery that would require interruption of DAPT. Antiplatelet bridge therapy using cangrelor, an intravenous P2Y inhibitor, has been studied as a potential option to ensure continuation of DAPT perioperatively. However, limited evidence exists supporting the off-label use of cangrelor bridge therapy to noncardiac procedures. We descr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…8 Retrospective studies of cangrelor bridging for NCS report either no bleeding or minor procedural bleeding (Table 4), suggesting that this is a safe approach to perioperative platelet inhibition. [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 Retrospective studies of cangrelor bridging for NCS report either no bleeding or minor procedural bleeding (Table 4), suggesting that this is a safe approach to perioperative platelet inhibition. [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the BRIDGE trial reported a low incidence of preoperative ischemic events, and retrospective studies of cangrelor bridging for NCS report a low incidence of perioperative MACE (Table 4). 8,[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] Thus, cangrelor bridging appears to be an effective approach for mitigating the risk of perioperative MACE.…”
Section: Table 4 (Continued)mentioning
confidence: 99%
“…22 To date, there is no randomized trial of bridging with cangrelor in NCS, and limited observational experience are available with heterogenous prescribing and monitoring practices, which may contribute to suboptimal outcomes. [10][11][12][13][14][15][16] Likewise, data on bridging use of short-acting GPIs are heterogeneous as well with regard to type of surgery, inclusion criteria, time windows between stent implantation or ACS and surgery, and antiplatelet strategies during the perioperative period which may partly explain the reported variability in success rates. 37 Despite the inclusion of a similar miscellaneous of surgical procedures, we believed that the strength of our study is a standardize case by case approach evaluation to weight the ischemic and bleeding risk and the use of a bridging protocol with a close postoperative monitoring which could have had a positive impact on our study findings.…”
Section: Discussionmentioning
confidence: 99%
“…9 However, there is limited reported data on the use of cangrelor among patients undergoing noncardiac surgery (NCS). [10][11][12][13][14][15][16] On this background, we report the results of a prospective, multicenter registry describing realworld experience of a prespecified bridging protocol using cangrelor conducted in patients referred to nondeferrable intermediate to high bleeding risk surgery requiring withdrawal of DAPT.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, case reports of successful cangrelor bridging describe variable dosing (range 0.25-4 µg/kg/min) and inconsistent use of PRUs to monitor efficacy of the drug. [66][67][68][69] Therefore, the efficacy of cangrelor at 0.75 µg/kg/min is based on a surrogate marker in a low-risk patient population, and the appropriate bridging dose of cangrelor remains debatable.…”
Section: Safety and Efficacy Of IV Antiplatelet Agentsmentioning
confidence: 99%